A booster of Delta-Omicron RBD-dimer protein subunit vaccine augments sera neutralization of Omicron sub-variants BA.1/BA.2/BA.2.12.1/BA.4/BA.5. Issue 1 (31st December 2023) - Duan, Minrun; Duan, Huixin; An, Yaling; Zheng, Tianyi; Wan, Shengfeng; Wang, Hui; Zhao, Xin; Dai, Lianpan; Xu, Kun; Gao, George F.
ABSTRACT: The SARS-CoV-2 Omicron variants of concern (VOCs) showed severe resistance to the early-approved COVID-19 vaccines-induced immune responses. The breakthrough infections by the Omicron VOCs are currently the major challenge for pandemic control. Therefore, booster vaccination is crucial to enhance immune responses and protective efficacy. Previously, we developed a protein subunit COVID-19 vaccine ZF2001, based on the immunogen of receptor-binding domain (RBD) homodimer, which was approved in China and other countries. To adapt SARS-CoV-2 variants, we further developed chimeric Delta-Omicron BA.1 RBD-dimer immunogen which induced broad immune responses against SARS-CoV-2 variants. In this study, we tested the boosting effect of this chimeric RBD-dimer vaccine in mice after priming with two doses of inactivated vaccines, compared with a booster of inactivated vaccine or ZF2001. The results demonstrated that boosting with bivalent Delta-Omicron BA.1 vaccine greatly promoted the neutralizing activity of the sera to all tested SARS-CoV-2 variants. Therefore, the Delta-Omicron chimeric RBD-dimer vaccine is a feasible booster for those with prior vaccination of COVID-19 inactivated vaccines.